Plant Evolution History Overwhelms Current Environment Gradients in Affecting Leaf Chlorophyll Across the Tibetan Plateau - He, Yicheng; Li, Tingting; Zhang, Ruiyang; Wang, Jinsong; Zhu, Juntao; Li, Yang; Chen, Xinli; Pan, Junxiao; Shen, Ying; Wang, Furong; Li, Jingwen; Tian, Dashuan (Frontiers in Plant Science, 2022)
Aims: Leaf chlorophyll (Chl) is a fundamental component and good proxy for plant photosynthesis. However, we know little about the large-scale patterns of leaf Chl and the relative roles of current environment changes versus plant evolutionary history in driving leaf Chl variations. Locations: The east to west grassland transect of the Tibetan Plateau. Methods: We performed a grassland transect over 1600 km across the Tibetan Plateau, measuring leaf Chl among 677 site-species. Results: Leaf Chl showed a significantly spatial pattern across the grasslands in the Tibetan Plateau, decreasing with latitude but increasing with longitude. Along with environmental gradient, leaf Chl decreased with photosynthetically active radiation (PAR), but increased with water availability and soil nitrogen availability. Furthermore, leaf Chl also showed significant variations among different functional groups (C4 > C3 species; legumes < non-legume species), but no difference between annual and perennial species. However, we surprisingly found that plant evolutionary time played a dominant role in shaping leaf Chl variations, when comparing the sum and individual effects of all the environmental factors above. Moreover, we revealed that leaf Chl nonlinearly decreased during plant evolutionary history. This well matches the nonlinearly increasing trend in PAR during the geological time-scale uplift of the Tibetan Plateau. Main conclusions: This study highlights the dominant role of plant evolutionary history in determining leaf Chl variations across the Tibetan Plateau. Given the fundamental role of Chl for photosynthesis, these results provide new insights into reconsidering photosynthesis capacity in alpine plants and carbon cycle in an evolutionary view.